Application of Gas-Kinetic BGK Scheme for Solving 2-D Compressible Inviscid Flow around Linear Turbine Cascade - Abdusslam, Saleh N.; Ong, Jiunn Chit; Hamdan, Megat M.; Omar, Ashraf Ali; Asrar, Waqar (Taylor & Francis, 2006)
Fluid flows within turbomachinery tend to be extremely complex. Understanding such flows is crucial in the effort to improve current turbomachinery designs. Hence, computational approaches can be used to great advantage in this regard. In this paper, gas-kinetic BGK (Bhatnagar-Gross-Krook) scheme is developed for simulating compressible inviscid flow around a linear turbine cascade. BGK scheme is an approximate Riemann solver that uses the collisional Boltzmann equation as the governing equation for flow evolutions. For efficient computations, particle distribution functions in the general solution of the BGK model are simplified and used for the flow simulations. Second-order accuracy is achieved via the reconstruction of flow variables using the MUSCL (Monotone Upstream-Centered Schemes for Conservation Laws) interpolation technique together with a multistage Runge-Kutta method. A multi-zone H-type mesh for the linear turbine cascades is generated using a structured algebraic grid generation method. Computed results are compared with available experimental data and found to be in agreement with each other. In order to further substantiate the performance of the BGK scheme, another test case, namely a wedge cascade, is used. The numerical solutions obtained via this test are validated against analytical solutions, which showed to be in good agreement.